Humor in Conversation: Flouting Maxims in the 'Close the Door' Podcast - Zelianti, Syafina; Degaf, Agwin; Baswarudin, Fuad; Guktomo, Guktomo (Universitas Islam Sultan Agung, 2024)
This study analyzes an episode of the